2015
DOI: 10.1249/mss.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Hamstring Strength and Hamstring Injury Risk in Australian Footballers

Abstract: Low levels of eccentric hamstring strength increased the risk of future HSI. Interaction effects suggest that the additional risk of future HSI associated with advancing age or previous injury was mitigated by higher levels of eccentric hamstring strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
313
4
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(352 citation statements)
references
References 28 publications
10
313
4
5
Order By: Relevance
“…Muscular strength, the maximum force or torque a muscle group can produce, is a major contributor to function in both athletic (Wisloff et al 2004) and day-to-day tasks (Samuel et al 2012), and is a risk factor for muscle injury (Opar et al 2015) as well as the development (Slemenda et al 1998) and progression (Amin et al 2009) of joint degeneration in osteoarthritis. Consequently, resistance training (RT) is frequently employed when aiming to: improve athletic performance (Wilson et al 1996;Comfort et al 2012); enhance mobility of middle-aged and older adults (Brochu et al 2002;Brandon et al 2003); reduce injury risk (Brooks et al 2006;Noyes and Barber Westin 2012); prevent or slow the progression of joint degeneration (Zhang and Jordan 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Muscular strength, the maximum force or torque a muscle group can produce, is a major contributor to function in both athletic (Wisloff et al 2004) and day-to-day tasks (Samuel et al 2012), and is a risk factor for muscle injury (Opar et al 2015) as well as the development (Slemenda et al 1998) and progression (Amin et al 2009) of joint degeneration in osteoarthritis. Consequently, resistance training (RT) is frequently employed when aiming to: improve athletic performance (Wilson et al 1996;Comfort et al 2012); enhance mobility of middle-aged and older adults (Brochu et al 2002;Brandon et al 2003); reduce injury risk (Brooks et al 2006;Noyes and Barber Westin 2012); prevent or slow the progression of joint degeneration (Zhang and Jordan 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, athletes with a history of ACL injury or HSI display similar eccentric knee flexor weakness and shorter BFLongHead fascicle lengths in previously injured limbs compared to the uninjured contralateral limbs (Opar et al, 2015a;Timmins et al, 2016b). These findings suggest that a prior ACL injury and HSI may both significantly increase the risk of future HSI.…”
Section: Program Of Researchmentioning
confidence: 83%
“…Previous work has shown that deficits in eccentric knee flexor strength during the performance of the Nordic hamstring exercise are associated with a 4.3 to 4.4-fold increased risk of future hamstring injury in elite Australian rules footballers (Opar et al, 2015a) and professional soccer players (Timmins et al, 2016b), although no such relationship was noted for Rugby players (Bourne et al, 2015). Meanwhile, athletes with a history of ACL injury or HSI display similar eccentric knee flexor weakness and shorter BFLongHead fascicle lengths in previously injured limbs compared to the uninjured contralateral limbs (Opar et al, 2015a;Timmins et al, 2016b).…”
Section: Program Of Researchmentioning
confidence: 99%
See 2 more Smart Citations